Recurrent Premature Rupture of Membranes in a Patient with Conservative Treatment Failure, Leading to Placental Abruption and Preterm Delivery: A Case Report. - Dwi Putra, Nanda Ghaffar; Kurniawan, Rommy Andika (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Introduction: Preterm Premature Rupture of Membranes in premature labor refers to the rupture of the amniotic sac before 37 weeks of gestation. PPROM is one of the most common complications during pregnancy and can lead to more serious risks for both the mother and the fetus. While premature labor is the most prevalent complication associated with PROM, it is important to note that placental abruption, though rare, can also occur concurrently.Case: A 24-year-old woman with a gestational age of 30-31 weeks has been treated conservatively at 27-28 weeks of gestation and returned to the hospital with complaints of watery discharge and blood spots. Physical examination found abdominal tenderness and defans. From the internal examination, it was found that there was no amniotic fluid with a cervical opening of 3-4 cm, and the bleeding was blackish-red. The patient was diagnosed with G2P1A0 (second pregnancy, one live birth, and no abortions) at 30-31 weeks with placental abruption lasting more than 24 hours and failed conservative treatment. An emergency cesarean section was performed and the infant was placed under NICU care.Discussion: The infection and inflammatory process following conservative treatment can be a cause behind placental abruption in mothers. The primary management approach involves monitoring the vital signs of both the mother and the fetus. This assessment is crucial in determining the best next steps, and a cesarean section is often expected to ensure the safety of both the fetus and the mother.Conclusion: Placental abruption is a serious obstetric emergency that can endanger both the mother and the fetus. The most prevalent cause of abruption is an infection inflammatory reaction in the uterus. While PPROM rarely triggers placental abruption, it did occur in this case.Rekurensi Ketuban Pecah Dini pada Pasien Gagal Perawatan Konservatif Yang Menyebabkan Solusio Plasenta dan Persalinan PrematurAbstrak Pendahuluan: Ketuban pecah dini pada persalinan prematur merupakan pecahnya lapisan ketuban sebelum usia 37 minggu. Ini merupakan kondisi komplikasi yang paling sering terjadi pada kehamilan dan dapat memunculkan komplikasi yang lebih serius pada ibu dan janin. Komplikasi ketuban pecah dini paling sering adalah pada persalinan prematur. Namun demikian, adanya solusio plasenta pada persalinan prematur masih jarang terjadi.Kasus: Wanita 24 tahun dengan usia kehamilan 30 - 31 minggu telah dirawat secara konservatif pada saat usia kehamilan 27 - 28 minggu datang kembali ke rumah sakit dengan keluhan keluar air dan bercak darah. Dari pemeriksaan fisik, diketahui adanya nyeri tekan pada perut dan defans. Saat pemeriksaan dalam, tidak ditemukan adanya ketuban, namun terdapat pembukaan pada serviks 3 - 4 cm dan adanya perdarahan berwarna merah kehitaman. Pasien didiagnosis dengan G2P1A0 30-31 minggu dengan solusio plasenta ketuban pecah dini durasi >24 jam dan gagal rawat konservatif. Dilakukan sectio cesarea emergensi dan perawatan NICU untuk bayi.Diskusi: Adanya proses infeksi-inflamasi post perawatan konservatif menjadi salah satu mekanisme terjadinya solusio plasenta pada ibu. Tatalaksana berupa pemantauan tanda vital ibu dan janin, ini menjadi prinsip utama dalam penentuan langkah berikutnya dan operasi sectio sesarea diharapkan dapat menyelamatkan janin dan ibu.Kesimpulan: Solusio plasenta merupakan salah satu kegawatdaruratan obstetri yang berpotensi membahayakan ibu dan janin. Ada banyak faktor pencetus solusio dan yang paling sering di antaranya adalah adanya reaksi infeksi-inflamasi dalam uterus. Ketuban pecah dini menjadi pencetus yang jarang ditemukan pada kasus solusio plasenta, namun ditemukan pada kasus ini.Kata kunci:Inflamasi, Infeksi, Ketuban Pecah Dini, Solusio Plasenta